The Role of Government Policies in Promoting Digital Agricultural Markets: A 2000-2024 Bibliometric Review - S, Yuvasri.; V, Dr. Selvam. (International Journal of Accounting and Economics Studies, 2025)
The digitalization of agricultural markets has become a transformative force, with government policies playing a pivotal role in promoting ‎market integration, transparency, and efficiency. This study conducts a bibliometric analysis of global equivalents to India’s e-National Ag-‎Agriculture Market (e-NAM), focusing on technology adoption, market efficiency, and policy frameworks. From an initial pool of 1,500 ‎research articles retrieved from Scopus and Web of Science, 285 relevant studies were selected for detailed analysis. The findings identify ‎major digital agricultural platforms worldwide, including the Farmers Market Coalition in the USA, EU-wide agricultural trade initiatives ‎under the Common Agricultural Policy (CAP), Australia’s National Farmers’ Federation digital programs, and China’s e-commerce-driven ‎agricultural trade systems. Comparative analysis reveals that the USA and EU emphasize regulatory frameworks and farmer cooperatives, ‎while China and Australia prioritize digital infrastructure and e-commerce-led–led integration. Despite notable progress, challenges persist ‎across regions, particularly regarding digital literacy, infrastructure limitations, and fragmented policy implementation. Bibliometric trends ‎show an increasing research focus on government interventions, digital infrastructure, and transparency mechanisms. The study underscores ‎the importance of enhancing platform interoperability, improving digital literacy among farmers, and fostering international collaboration. ‎These insights provide actionable policy recommendations for strengthening digital agricultural markets and ensuring long-term sustainability-‎ity through informed governance and technological innovation.